Antimicrobial Susceptibility of Vibrio Species Isolated From Brackish Water Shrimp Culture Environment - Hossain, M S; Aktaruzzaman, M; Fakhruddin, A N M; Uddin, M J; Rahman, S H; Chowdhury, M A Z; Alam, M K (Journal of Bangladesh Academy of Sciences, 2012)
A comparative study regarding prevalence and antimicrobial susceptibility of Vibrio species in the black tiger shrimp (Penaeus monodon Fabricius) culture environment as well as market samples were analyzed. Total Vibrio counts were found to range up to 2.5 × 103 cfu/gm and 60 cfu/gm in shrimp and Gher water samples, respectively. Results revealed that the total vibrio count were found to be higher in samples taking from the market shops in Dhaka city than Gher shrimp samples and the live shrimps were not contaminated with Vibrio species but dead shrimps were found contaminated, which were collected from shrimp Gher. In the antimicrobial susceptibility test, highest 28.57% resistance among total Vibrio isolates was observed to penicillin and cephalexin. Among the seven isolates of Vibrio species from Gher water sample one isolate displayed multi-drug resistance (MDR). The main reason of antibiotic resistance could be the indiscriminate application of antibiotics in shrimp farming and release of shrimp pond effluent to estuarine ecosystems or post harvest contamination of shrimps with the antibiotic resistant bacteria through the environment and human handling. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12964 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 213-220, 2012